Clinical Application of Stereotactic Body Radiotherapy (SBRT): Cranium to Prostate - Dwight E. Heron (Frontiers Research Topics, 2016)
Stereotactic radiosurgery is a relatively recent radiation technique initially developed using a frame-based system in 1949 by a Swedish neurosurgeon, Lars Leksell, for lesions not amendable to surgical resection. Radiosurgery is founded on principles of extreme radiation dose escalation, afforded by precise dose delivery with millimeter accuracy. Building upon the success of frame-based radiosurgery techniques, which were limited to cranial tumors and invasive head-frame placement, advances in radiation delivery and image-guidance have lead to the development of stereotactic body radiotherapy (SBRT). SBRT allows for frameless delivery of dose distributions akin to frame-based cranial stereotactic radiosurgery to both cranial and extra-cranial sites and has emerged as a important treatment strategy for a variety of cancers from the cranium to prostate. Herein we highlight ongoing investigations for the clinical application of SBRT for a variety of primary and recurrence cancers aimed at examining the growing clinical evidence supporting emerging roles for SBRT in the ever growing oncologic armamentarium.